Malaria in the mosquito - Billingsley, Peter (Henry Stewart Talks, 2011)
Malaria: one of the world's foremost killers, Malaria in the mosquito, The mosquito midgut -- Exflagellation, Ookinetes, Antibodies block transmission to mosquito, CTRP KO results in loss of infectivity to mosquito, The time bomb theory of ookinete invasion, Oocysts, Interactions between Plasmodium and mosquito midgut, Insect immunity, Sporozoites, A sporozoite based malaria vaccine, Dynamics of Malaria in the mosquito